Tumour necrosis factor superfamily members in ischaemic vascular diseases. Issue 4 (28th February 2019) - Nash, Megan; McGrath, Jordan P; Cartland, Siân P; Patel, Sanjay; Kavurma, Mary M
Abstract: Current treatment of ischaemic vascular diseases such as coronary and peripheral artery disease includes angioplasty and bypass grafting, as well as lipid lowering therapies and control of other cardiovascular risk factors. Numerous members of the tumour necrosis factor superfamily (TNFSF) have recently shown emerging roles in both the protection and progression of such diseases. Understanding the role TNFSF members play in ischaemic vascular disease may provide insight into the development of novel therapeutics to prevent or treat diseases relating to atherosclerosis and ischaemia. This review summarizes the most recent findings relating to TNFSF members and the mechanisms that precede ischaemic vascular disease progression, particularly endothelial dysfunction, chronic inflammation, and atherosclerotic plaque development. This review also explores recent translational research on the role of TNFSF therapies in cardiovascular disease.